2008
DOI: 10.1096/fj.08-124248
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor is critical to interleukin‐5‐driven eosinophilopoiesis and tissue eosinophilia triggered by Schistosoma mansoni infection

Abstract: Macrophage migration inhibitory factor (MIF) participates in the pathogenesis of inflammatory diseases, including asthma, in which it enhances airway hypersensitivity and tissue eosinophilia. Herein, we investigated the role of MIF in eosinophilopoiesis and tissue eosinophilia using Schistosoma mansoni infection. MIF-deficient (Mif(-/-)) mice had similar numbers of adult worms, eggs, and granulomas compared to wild-type mice, but the size of granulomas was strikingly reduced due to smaller numbers of eosinophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 54 publications
3
39
2
2
Order By: Relevance
“…Eosinophils express CXCR4 and migrate toward CXCR4 ligand SDF-1 to a similar extent as eotaxin [46] and CXCR4 blockade suppresses eosinophil migration into the asthmatic lung [47]. Although further studies are needed to differentiate between MIF and SDF-1 in the eosinophil migration into the lung, MIF can act as a chemoattractant for eosinophils [48], suggesting a direct role for MIF in eosinophil migration into inflamed lung tissue. Additionally, TRX has been shown to act as inhibitor of eosinophil chemotaxis in response to eotaxin [49].…”
Section: Discussionmentioning
confidence: 99%
“…Eosinophils express CXCR4 and migrate toward CXCR4 ligand SDF-1 to a similar extent as eotaxin [46] and CXCR4 blockade suppresses eosinophil migration into the asthmatic lung [47]. Although further studies are needed to differentiate between MIF and SDF-1 in the eosinophil migration into the lung, MIF can act as a chemoattractant for eosinophils [48], suggesting a direct role for MIF in eosinophil migration into inflamed lung tissue. Additionally, TRX has been shown to act as inhibitor of eosinophil chemotaxis in response to eotaxin [49].…”
Section: Discussionmentioning
confidence: 99%
“…IL-5 KO mice had virtually no eosinophils in either saline-sensitized skin or in OVA-sensitized skin (Spergel et al, 1999). Recently, Magalhães et al (2009) reported that MIF was involved in IL-5-driven maturation of eosinophils and in tissue eosinophilia associated with Schistosoma mansoni infection. In addition, several earlier studies demonstrated that MIF KO mice failed to develop tissue eosinophilia, and that eotaxin, IL-4, and IL-5 were not induced in either allergic lung tissues or bronchoalveolar lavage fluid (Mizue et al, 2005;Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The Arthus reaction is a consequence of a hypersensitivity reaction caused by the formation and deposition of immune complexes (IC, combined antigen and antibody), which occur in the presence of elevated levels of preformed antibodies in a previously vaccinated person. The deposition of IC triggers Fc gamma receptor-dependent inflammation, in which macrophages recognize IC and release migration inhibitory factor (MIF), that damages surrounding tissue [66,67]. The cascade of events involved in the Arthus reaction includes the spastic contraction of the arterioles, endothelial damage, formation of leukocyte thrombi, exudation of fluid and blood cells into the tissues, and sometimes ischemic necrosis, which can be mistakenly diagnosed as DTH [68][69][70].…”
Section: Arthus Reactionmentioning
confidence: 99%